1989
DOI: 10.1016/0378-1097(89)90022-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid transfer between Pseudomonas spp. within epilithic films in a rotating disc microcosm

Abstract: Pseudomonas putida Pseudomonas fluorescens pQM1Rifampicin and nalidixic acid resistant mutants were selected as described previously [13].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Conjugal transfer of plasmids has been shown to occur in soil (19,29,30,32), wastewater (22,27,30), and aquatic systems (13,15,27,30,32) in both laboratory microcosms and in situ (2,4,6,26,29). For example, have shown plasmid transfer between natural freshwater bacteria in river epilithon.…”
mentioning
confidence: 99%
“…Conjugal transfer of plasmids has been shown to occur in soil (19,29,30,32), wastewater (22,27,30), and aquatic systems (13,15,27,30,32) in both laboratory microcosms and in situ (2,4,6,26,29). For example, have shown plasmid transfer between natural freshwater bacteria in river epilithon.…”
mentioning
confidence: 99%
“…Although a simple one-step transfer of conjugative plasmids has been demonstrated in various fresh surface waters for coliforms (12,13) and Pseudomonas strains (4,22,26), it has not been demonstrated in drinking water. Two-stage mobilization of nonconjugative plasmids carrying cloned foreign DNA has not been demonstrated in any type of fresh water.…”
mentioning
confidence: 99%
“…Conjugative gene transfer typically ranges from 10 −9 to 10 −2 transconjugants per recipient within natural complex biofilms [15,16]. In our study we have shown that the IncP plasmid pQKH6 can be conjugatively transferred between isogenic P. putida strains at mean frequencies of up to 8.40×10 −4 transconjugants per recipient in the biofilm of sewage filter beds.…”
Section: Discussionmentioning
confidence: 67%